PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MENGGUNAKAN MEDIA INTERAKTIF BAAMBOOZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN KREATIVITAS, INOVASI DAN KEWIRAUSAHAAN DI KELAS XI MPLB SMKN 1 MEDAN - Lubis, Sapriani Nur Adilah; Nelly Armayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model using Baamboozle interactive media on students’ critical thinking skills in the subject of Creativity, Innovation, and Entrepreneurship at class XI MPLB SMKN 1 Medan. This research employed a quantitative approach with an experimental method. The population consisted of all students of class XI MPLB SMKN 1 Medan in the academic year 2025/2026. The samples were class XI MPLB 4 as the experimental class consisting of 33 students and class XI MPLB 3 as the control class consisting of 35 students, selected through purposive sampling. Data collection techniques used pretest and posttest instruments in the form of 25 multiple-choice questions based on Bloom’s taxonomy levels C4 to C6. The data were analyzed using Independent Sample t-test and N-Gain analysis. The results showed that the average posttest score of the experimental class was 81.64, higher than the control class which was 75.40. The Independent Sample t-test result obtained a significance value of 0.018 < 0.05, indicating that there was a positive and significant effect of the Problem Based Learning model using Baamboozle interactive media on students’ critical thinking skills. In addition, the N-Gain score of the experimental class was 45.44 in the moderate category, while the control class obtained 29.91 in the low category. Therefore, the application of the Problem Based Learning model assisted by Baamboozle interactive media can improve students’ critical thinking skills better than conventional learning.